(untitled) (Raparin Journal of Humanities (RJH), 2022)
It is true that, from the beginning, philosophy and religion were two separate areas and subjects; each of which interacted with contemporary problems and issues in its own way and worldview. If they were not compatible then, they did not oppose each other. In other words, the connection between religion and philosophy did not become a problem from the beginning. This was because each of them independently worked on their own issues and problems by themselves. However, with the advent of Islam and its opening up to the outside world, it came into conflict with the thinking and philosophy of other nations in the region, especially with Greek thought and philosophy; this also became an important issue and a clear problem for Islamic scholars and philosophers and divided them into two separate factions. One of them was completely hostile to philosophy and rejected any compromise and interaction between Islam and Greek philosophy, considering only religion as the main source of science and knowledge, and outside of religion, they did not accept anything. However, the other faction, most of whom were Islamic philosophers, advocated a compromise between religion and philosophy, seeking to create a kind of compromise and coexistence between them, and to show the fact that there is no incompatibility or opposition between the two. Within this context Ibn Rushd had a clear and important role in this regard. He made great efforts to make everyone aware of the fact that philosophy and religion do not have any incompatibility and conflict between them, and they are able to exist or occur together. To this end, he resorted to a set of important rules such as rational and narrative arguments in order to be able to tell all opponents that they have made a mistake in rejecting and opposing philosophy. He also showed everyone through these rules that philosophy and religion are friends and compatible with each other, that is, philosophy and religion are complementary to each other and they are inherently friends and internally have the same soul.